Clinico‐genetic comparisons of paroxysmal kinesigenic dyskinesia patients with and without PRRT2 mutations. (29th March 2013) - Tan, L. C. S.; Methawasin, K.; Teng, E. W. L.; Ng, A. R. J.; Seah, S. H.; Au, W. L.; Liu, J. J.; Foo, J. N.; Zhao, Y.; Tan, E. K.
<x xml:space="preserve">Abstract</x> Background and purpose Mutations in the PRRT2 gene have been identified in patients with paroxysmal kinesigenic dyskinesias (PKD); however, not many detailed clinico‐genetic correlations have been performed. Methods To investigate PRRT2 mutations in a mixed Asian PKD population and perform clinico‐genetic correlations, we recruited patients between 2002 and 2011 and administered a standardized questionnaire. Results Amongst 29 unrelated patients with PKD recruited, five PRRT2 mutations were present in 15 patients. Three mutations (c.649dupC, c.649delC, c.649C>T) were previous reported, while three were novel mutations (c.604delT; c.609_611delACC/p.Ser202Hisfs; c.697_698delAG/p.Ser233Trp fsX5). Clinico‐genetic correlations revealed that a history of seizures was more common in patients with PRRT2 mutations, although this did not reach statistical significance (P= 0.08). A younger age of onset, non‐Chinese, and the presence of premonitory sensations were significantly associated with PRRT2 mutations in the univariate analysis. Multivariate logistic regression analysis demonstrated that age of onset [odds ratio (OR) = 0.59, P = 0.025] and premonitory sensation (OR = 10.67, P = 0.028) were independently associated with positive PRRT2 mutation. Conclusions PRRT2 mutations are common in patients with PKD, and a double PRRT2 mutation is reported for the first time. PRRT2 mutations are significantly associated with a younger age of onset and the presence of premonitory sensation in our population.